O interesse e a observação no processo de alfabetização científica em Geografia - Vieira, Naiara Anhasco Sotano [UNIFESP] (2020)
In this research we investigate the potentialities of the notion of interest (DEWEY, 1971; 1979) and analytical observation (DEWEY, 1979) in the process of scientific literacy in Geography. Therefore, in the construction of the learning proposal we chose the concept of landscape and the categories of analysis of the geographical space presented by Milton Santos (2014a; 2014b; 2014c). We propose a didactic sequence aiming to identify and analyze the students' interests; identify previous knowledge about the concept of the landscape; perceive the development of broad observation for analytical observation; and identify possible signs of scientific literacy in Geography. Both in the proposal for the construction of the didactic sequence and the analysis of the data, our references were Gomes (2013, 2017), Santos (2014a, 2014b, 2014c) and Dewey (1971, 1979). The research was carried out with sixth-year students, in a private school in São Paulo and, to carry it out, we made use of action research with an emphasis on cooperative action research (TRIPP, 2005). We suggested raising hypotheses about the concept of landscape through the realization of drawings and texts, initially with the use of broad observation. We suggested activities to direct the eye towards a new realization of drawings and production of texts. The data were collected through analysis and categorization of the drawings and a qualitative comparison of the texts. We identified that considering the notion of interest of the students was important in the class organization; to realize the use of imagination and memory in the construction of thought, and to identify the previous knowledge. After the application of the classes prepared to direct the eye through geographical categories, some students started to use observation in a more analytical way looking in the landscape, data that could provide a basis for the reasoning they were building. Thus, they stopped using observation only for contemplation and could use it more scientifically, with a geographical eye.